Activity Assay and Determination of Active Larvicidal Compounds from Cat's Whiskers (Orthosiphon aristatus Blume miq.) - Guntina, Rizka Khoirunnisa; Riyanti, Soraya; Faramayuda, Fahrauk (Fakultas Kedokteran Universitas Sriwijaya, 2025)
The tropical climate of Indonesia presents a significant risk for the prevalence of various mosquito-borne diseases, particularly Dengue Hemorrhagic Fever (DHF), which has become a critical public health concern in recent years. The control of mosquito populations, specifically targeting larvae, is a strategic approach in managing the transmission of DHF. Traditional methods involving synthetic larvicidal agents, however, raise concerns regarding potential resistance among mosquito populations and adverse effects on human health. Consequently, there exists an urgent need for alternative solutions that are both effective and safe for human exposure. One promising avenue is the exploration of natural larvicidal agents sourced from local flora, such as the white-purple variety of cat's whiskers (Orthosiphon aristatus Blume miq.). This study investigates the larvicidal potential of this plant, focusing on its main secondary metabolites, namely flavonoids and phenolics, which are hypothesized to possess larvicidal activities. Conducted extensive larvicidal activity assaying on various extracts and fractions derived from the white-purple cat's whiskers. Notably, the ethyl acetate fraction demonstrated superior efficacy, evidenced by a calculated LC50 value of 737.71 ppm, underscoring its potential as a sustainable larvicidal agent. Subsequent analyzes of this active fraction revealed the presence of the compound sinensetin, which further validates the insecticidal application of this plant in controlling mosquito populations effectively. This research contributes to the paradigm shift toward natural alternatives in pest management, highlighting the importance of harnessing local biodiversity in the fight against vector-borne diseases.